Increased volume and collagen crosslinks drive soft tissue contribution to post-traumatic elbow contracture in an animal model - Dunham, Chelsey L. (J Orthop Res, 2020)
Post-traumatic joint contracture (PTJC) in the elbow is a biological problem with functional consequences. Restoring elbow motion after injury is a complex challenge because contracture is a multi-tissue pathology. We previously developed an animal model of elbow PTJC using Long-Evans rats and showed that the capsule and ligaments/cartilage were the primary soft tissues that caused the persistent joint motion loss. The objective of this study was to evaluate tissue specific changes within the anterior capsule and lateral collateral ligament (LCL) that led to their contribution to elbow contracture. In our rat model of elbow PTJC, a unilateral surgery replicated damage that commonly occurs due to elbow dislocation. Following surgery, the injured limb was immobilized for 42 days. The capsule and LCL were evaluated after 42 days of immobilization or 42 days of immobilization followed by 42 days of free mobilization. We evaluated extracellular matrix protein biochemistry, non-enzymatic collagen crosslink content, tissue volume with contrast enhanced micro-computed tomography, and tissue mechanical properties. Increased collagen content, but not collagen density, was observed in both injured limb capsules and LCLs, which was consistent with the increased tissue volume. Injured limb LCLs exhibited decreased normalized maximum force, and both tissues had increased immature collagen crosslinks compared to control. Overall, increased tissue volume and immature collagen crosslinks in the capsule and LCL drive their contribution to elbow contracture in our rat model.